(untitled) (Modern education and development, 2025)
Language is not only a medium of communication but also a fundamental pillar in the formation, transmission, and evolution of culture. This article examines the intricate relationship between language and cultural evolution, exploring how language enables the preservation of collective memory, facilitates and the sharing of beliefs and practices, and supports the development of social norms identities. Drawing upon insights from anthropology, linguistics, and cultural studies, the paper highlights the indispensable role of language in shaping and sustaining cultures across history and geography.